Perlindungan Anak: Tinjauan HR. Abu Dawud No. 494 dan Pasal 1 Ayat (2) UU No. 35 Tahun 2014 - Fathsa, Rafy Muhammad; Arifin , Tajul (Indo Publishing, 2025)
This article was made to analyze how to educate children in carrying out prayer according to the hadith narrated by Abu Dawud number 494 with Article 1 paragraph (2) of Law Number 35 of 2014 concerning child protection. The results of the study show that the hadith narrated by Abu Dawud number 494 encourages parents to beat their children who are 10 years old if they do not perform prayers. This seems to be contrary to Article 1 paragraph (2) of Law Number 35 of 2014, which states that child protection includes all activities that guarantee and protect children and their rights to live, grow, develop, and participate optimally in accordance with the dignity and dignity of humanity, and are protected from discrimination and violence. The purpose of this article is to align the content of the hadith with the study of positive Indonesian law and to find out whether the action has a psychological impact.